Uji validasi Mayo Cardiac Intensive Care Unit Admission Risk Score (M-CARS) untuk menilai mortalitas selama rawatan pada pasien Cardiovascular Care Unit (CVCU) di RSUP Haji Adam Malik - Siahaan, Basten Jeremiah; Hasan, Refli; Sitepu, Andika (The Indonesian Heart Association, 2022)
Background: Approximately 85% of all in-hospital deaths occur in Cardiovascular Care Unit (CVCU) where M-CARS will be an important starting point for development of CVCU-specific mortality risk prediction models. Aim: This research aims to assess M-CARS validation to assess mortality during treatment in CVCU patients at Haji Adam Malik (HAM) General Hospital. Methods: This research is a prospective research that examines M-CARS score validity as a predictor of intra-hospital mortality in patients treated at CVCU HAM General Hospital Medan from September 2021 - January 2022. If correlation test results show a significant relationship, cut-off value M-CARS score will be taken using ROC (Receiver Operating Characteristic) curve analysis, then analysis of M-CARS score diagnostic value will be carried out according to cut-off value obtained to predict mortality during hospitalization. Then Hosmer-Lemeshow test was carried out to assess suitability of logistic regression on risk prediction assessment within population that being assessed. Results: M-CARS had a very good discriminatory ability (AUC 0.93) to predict intrahospital mortality. The calibration value using Hosmer Lemeshow test (R2 = 0.982; p = 1.516; p>0.05) shows that there is no significant difference between observed and expected mortality rate by two scoring systems therefore considered as accurate. Conclusion: M-CARS is valid to be used in assessing risk of mortality events during CVCU treatment at H. Adam Malik Hospital Medan. This article has a related Erratum.